Hi. This post will be quick and dry (just like sex with your wife, hahaha). Yes, an extremely scary-looking exercise. But it's actually a very similar process to what I did in 2.12b . In fact, it's even
easier.
Letting θ denote the k[{zij}] → k[x0,…,xr,y0,…,ys] map the hint gave us, we set α = ker θ and we wanna
show that imϕ = Z(α).
"One inclusion is easier than the other," said 2.12b, and the statement holds analogously here. Give me a point
P = (a0,…,ar) × (b0,…,bs) ∈ Pr × Ps, so that ϕ(P) = (…,aibj,…). Now give me an f(…,zij,…) ∈ α.
f(…,zij,…) | ∈ ker θ | |
|
θ(f(…,zij,…)) | = 0 | |
|
f(…,θ(zij),…) | = 0 | |
|
f(…,xiyj,…) | = 0 | |
|
f(…,ai,bj,…) | = 0 | |
|
f(ϕ(P)) | = 0 | |
|
| | |
Since
f ∈ α was arbitrary,
ϕ(P) ∈ Z(α). And since
P was arbitrary, im
ϕ ⊂ Z(α) Now for the reverse inclusion. Given
C = (…,cij,…) ∈ Z(α), can we find
P = (a0,…,ar) × (b0,…,bs) ∈ Pr ×Ps
such that
ϕ(P) = C I.e. we need to satisfy
(…,aibj,…) = (…,cij,…).
I.e. we need to satisfy
aibj = cij (up to a constant multiple independent of i,j).
So what do we do? Same thing in 2.12b: Line up the requirements, "force" values for our
ai,bjs, verify that they
actually work.
First, I'll assume that
c00≠0 without loss of generality. Now, let
a0 be.... anything but zero. Yes. You heard me
right. Let
a0 be literally
fucking anything you want it to be, reader, as long as it's nonzero and from
k.
Then check out these requirements:
a0b0 | = c00 | a0b0 | = c00 | | | |
|
a0b1 | = c01 | a1b0 | = c10 | | | |
|
![.
..](Ip2p145x.png) | |
![.
..](Ip2p146x.png) | | | |
|
a0bj | = c0j | aib0 | = ci0 | | | |
|
![.
..](Ip2p147x.png) | |
![.
..](Ip2p148x.png) | | | |
|
a0bs | = c0s | arb0 | = cr0 | | | |
|
| | | | |
As soon as
a0 is fixed, so is everything else:
b0 | = c00∕a0 | a0 | = c00∕b0 | | | |
|
b1 | = c01∕a0 | a1 | = c10∕b0 | | | |
|
![...](Ip2p149x.png) | |
![...](Ip2p1410x.png) | | | |
|
bj | = c0j∕a0 | ai | = ci0∕b0 | | | |
|
![...](Ip2p1411x.png) | |
![...](Ip2p1412x.png) | | | |
|
bs | = c0s∕a0 | ar | = cr0∕b0 | | | |
|
| | | | |
So choosing
anything for
a0 forces all of
P. Now we just have to check that
ϕ(P) does indeed equal
C. I.e. we need
to check if
aibj = cij. Well, based on our settings,
aibj | =
![ci0c0j
a0b0](Ip2p1413x.png) | |
|
| =
![ci0c0j
------
c00](Ip2p1414x.png) | |
|
| | |
Now suppose, for the sake of contradiction,
![ci0c0j-
c00](Ip2p1415x.png)
did NOT equal
cij. Then that would mean
![ci0c0j
-c----
00](Ip2p1416x.png) | ≠cij | |
|
ci0c0j | ≠cijc00 | |
|
ci0c0j - cijc00 | ≠ 0 | |
|
| | |
I.e. we'd have that
C does NOT satisfy the polynomial
But, of course,
θ(g) | = xiy0x0yj - xiyjx0y0 | |
|
| = 0 | | |
So
g ∈ ker θ i.e.
g ∈ α. By assumption,
C ∈ Z(α), yielding a contradiction.
Don't worry. The next exercise is another 3-parter.